Volumetric and dosimetric comparison of two delineation guidelines for the radiation treatment of laryngeal squamous cell carcinoma. (November 2019) - Bondue, C.; Racadot, S.; Coutte, A.; Dupuis, P.; Biston, M.C.; Grégoire, V.
Highlights: The delineation of target volumes for Head and Neck IMRT is complex. There have been several approaches for the delineation of the primary tumor clinical target volume: the anatomical guidelines, the geometric guidelines and more recently the international guidelines. Abstract: Purpose: Three methods have been recently proposed for the delineation of the primary tumor clinical target volume (CTV-P) in Head and Neck Cancers: the anatomic method popularized in the French literature by Lapeyre et al. the geometric methods proposed by the DAHANCA group, and more recently the international guidelines promoted by Grégoire et al. integrating the latter two. The aim of this study was to perform a volumetric and dosimetric comparison of the French and the International consensus methods in laryngeal SCC. Patients and methods: Two radiation oncologists independently delineated the high dose and low dose primary tumor CTV in four patients with T2 or T3 N0-M0 laryngeal SCC following either the so-called French guidelines or the International guidelines. For the 4 cases, the GTV was delineated by a single radiation oncologist. Nodal CTVs were delineated by one radiation oncologist for the 4 cases using International guidelines. Dose optimization was then performed with VMAT (MONACO version 5.11) using 6 MeV photons. Differences in target volumes and dose distributions in OARs and PTVs were then evaluated with various metrics such as the DICE Similarity Coefficient and the homogeneity index. Results: Major differences were observed in the CTV delineation between the 2 delineation methods for the low dose volumes and to a lower extend for the high dose volumes. These differences translated into variations in dose distribution favoring the International guidelines for decreasing dose to various OARs. Such differences toned down when dose distribution on the primary tumors PTVs and nodal PTVs were combined. Conclusion: This study demonstrated large differences in CTV delineation between the 2 delineation guidelines. Such differences translated into differences in dose distribution.